Stocks for the long run : the definitive guide to financial market returns and long-term investment strategies - Siegel, Jeremy J. (New York : McGraw-Hill, 2002)
The book provides investors with the strategies, tools, and techniques necessary to build significant stock market wealth.
Includes bibliographical references and index.
rua 24/09/14, opc 29/09/16
Loans
Keywords: Stocks; Stocks - history; Stocks - Rate of return; Rate of return